P262 Skeletal tuberculosis – a retrospective review at two inner City UK Hospitals. (12th November 2015) - Hagan, GC; Piper, J; Bagnall, H; Ahmed, I; Nathani, N
Abstract : Introduction and objectives: Skeletal tuberculosis (TB) accounts for about 10% of extrapulmonary tuberculosis in Europe and the USA. 1 Outcomes and duration of treatment are less well described than pulmonary TB. We sought to identify characteristics and outcomes for patients diagnosed with skeletal TB in the two hospitals in our trust. Methods: Cases of TB treated in our NHS trust from 1/1/2011 to 31/12/2013 with site of disease including bone and/or spine were included. Data was obtained from the Enhanced TB Surveillance Database and case note review. Patients with a positive alternative diagnosis were excluded. TB affecting other body systems was defined as imaging abnormalities with exclusion of alternative diagnoses. Results: 34 patients (20 males), mean age 42.7 years, were identified. 29(85%) were born outside the UK. No patients were HIV positive (test not offered/refused in 11%). Sites of disease are shown in Table 1 . 13(38%) of patients had the diagnosis made via non-surgical biopsy (either radiological or bedside), 6(18%) through surgical biopsy, and 5(15%) of patients having the diagnosis made through sampling from another site (usually pulmonary). The remainder of patients (10) either had a clinico-radiological diagnosis or the diagnosis made overseas, with 4 of those patients undergoing a non-diagnostic biopsy. Mean length of treatment was 10 months. At end of treatment 9(40%) of spinal TB patients had ongoing back pain and 4(33%) of patients with appendicular joint involvement had residual stiffness. Conclusions: Bedside or image guided procedures have a role in diagnosis of skeletal TB; about 30% will also have pulmonary TB which may be more accessible for diagnosis. Sending for TB culture during surgery is important. After appropriate treatment a proportion of patients have residual pain and stiffness. Reference: 1 Pigrau-Serrallach C, Rodríguez-Pardo D. Bone and joint tuberculosis. Eur Spine J . 2013;22 (Suppl 4):556–566